A gradient ultra-low resistivity electrode steel and a manufacturing method thereof
By designing the composition and process of the ultra-low resistivity electrode steel in the gradient, the problems of high resistivity and short life of cathode materials in the prior art are solved, and the resistivity and life are reduced, energy consumption is increased, and pollution is reduced.
Patent Information
- Application Number
- CN202310714851.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-16
AI Technical Summary
The cathode material Q195 used in the existing electrolytic aluminum process has a high resistivity, resulting in large power consumption, and the current passing through the material in different parts causes damage, shortening the material life.
By designing the composition and manufacturing process of ultra-low gradient resistivity electrode steel, the finished electrode steel has low central resistivity, high surface resistivity, and current passes from the center. Optimized steel composition and processes such as converter smelting, LF furnace refining, RH vacuum treatment, continuous casting, heating, rolling and other steps control the grain size gradient, thereby reducing resistivity and improving material strength.
It has achieved a reduction in resistivity of more than 35%, extends the service life of electrode steel, saves energy consumption, and reduces pollution caused by coal power generation.
Smart Images

Figure BDA0004288926900000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a gradient ultra-low resistivity electrode steel and a manufacturing method thereof. Background Art
[0002] In the electrolysis of aluminum, carbon is used as the anode and aluminum liquid is used as the cathode. A strong current is passed through the aluminum oxide at 950℃-970℃ to obtain aluminum. The electrode steel is used as the cathode conductive material in the electrolysis of aluminum. It is required to have a low resistivity to reduce the energy consumption. At present, the northern part of my country mainly relies on coal-fired power generation, which has caused a lot of pollution. The electrolytic aluminum industry is a large power consumer. Reducing the resistivity of the electrode steel in the electrolysis of aluminum can greatly reduce power consumption and save energy.
[0003] The cathode of aluminum electrolysis in my country is made of materials such as Q195, which has high resistance. The resistance inside and outside the material does not change much. The aluminum electrolysis process consumes huge amounts of electricity and the cost is quite high. Since the resistance inside and outside the material is consistent, the current passes randomly along different parts of the cathode material, causing damage to multiple parts of the material, greatly reducing the life of the cathode material. Summary of the invention
[0004] The purpose of the present invention is to provide a gradient ultra-low resistivity electrode steel and a manufacturing method thereof. The low resistivity of the electrode steel is further reduced through component design, and the resistivity of the electrode steel is made to be gradient distributed through the preparation process, with low central resistivity and high surface resistivity. The current passes through the central part of the flat steel, thereby reducing the power consumption during the aluminum electrolysis process.
[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0006] A gradient ultra-low resistivity electrode steel, the mass percentage of its components are as follows: C: 0.001-0.003%, Si: 0.0005-0.001%, Mn: 0.008-0.01%, P≤0.006%, S≤0.002%, O: 0.002-0.003%, Cu: 4.3-5.2%, and the rest are Fe and impurity elements.
[0007] In the optimized scheme, the mass percentages of the components are: C: 0.001-0.003%, Si: 0.0005-0.001%, Mn: 0.008-0.01%, P≤0.006%, S≤0.002%, O: 0.0005-0.001%, Cu: 4.3-5.2%, and the rest are Fe and impurity elements.
[0008] The manufacturing method of the above-mentioned gradient low resistivity electrode steel comprises the steps of molten iron desulfurization, converter smelting, LF furnace refining, RH vacuum treatment, continuous casting, heating, rolling and cooling;
[0009] The converter smelting time is 30-35min, the slag removal process is twice, the tapping temperature is 1610-1620℃, and Cu is added during the tapping process;
[0010] The basicity of LF furnace refining slag is controlled at 3.2-3.7, and the LF furnace treatment time is not less than 30 minutes;
[0011] The decarburization time of RH vacuum treatment is greater than 16 minutes, and the oxygen content at the exit is 0.0006-0.0008%;
[0012] The temperature of the tundish is controlled at 1550-1570℃, and the cross-sectional size of the ingot is 280×380mm;
[0013] The heating temperature of the casting is 830-850℃, and the heating time is 160-210min;
[0014] The starting rolling temperature of the rough rolling is ≤800°C; the final rolling temperature of the fine rolling is ≤680°C, and the steel is rolled into a square steel of (170-230)×(120-160)×(2000-2100) mm in length; the steel is naturally cooled after rolling, and the cooling rate is 0.2-0.8°C / s.
[0015] According to the above scheme, in the converter smelting step, the secondary slag removal process controls the steel tapping temperature to 1615-1618°C.
[0016] According to the above scheme, in the LF furnace refining step, the leaving station temperature is 1690±10°C.
[0017] According to the above scheme, in the RH vacuum treatment step, the treatment time is ≥16 min with a vacuum degree of ≤60 Pa.
[0018] According to the above scheme, in the continuous casting step, a large tank long nozzle and a crystallizer submerged nozzle are used for protective casting, and the immersion depth is 82-92 mm; the temperature of the molten steel in the middle package is controlled to be 20-35°C above the liquidus temperature line of the steel grade; and the billet drawing speed is controlled to be 0.5-0.7 m / min.
[0019] According to the above scheme, in the heating step, the heating temperature of the ingot is controlled to be 845-850°C.
[0020] According to the above scheme, in the rough rolling step, the starting rolling temperature is controlled to be 780-800°C.
[0021] According to the above scheme, in the finishing rolling step, the final rolling temperature is controlled to be 650-680°C.
[0022] According to the above scheme, in the cooling step, the cooling rate is 0.7-0.8°C / s to cool to room temperature.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention adopts steel composition design to deeply remove C, Si and Mn elements in the steel, thereby reducing the hindering effect of impurity elements in the steel on the flow of electrons; adopts ultra-low O elements to reduce the presence of oxides in the steel and reduce the hindering effect of oxides on the movement of electrons; adds 4.3-5.2% of Cu elements to fill atomic vacancies and increase the conductivity of the phase interface, thereby improving the conductive performance of the material. Compared with ordinary Q195 material, the resistivity is reduced by more than 35%.
[0026] The invention controls the heating temperature of the ingot to 830-850°C, controls the final rolling temperature to be ≤680°C, and rolls the ingot into square steel with a length of (170-230)×(120-160)×(2000-2100) mm by low temperature rolling. The finished product forms a grain size gradient from the core to the surface, wherein the core grains are coarse and the surface grains are fine, and the grain size gradually increases from level 1 to level 5 from the core to the surface. Since the core grain size is large and the electrical conductivity is strong, the current selectively passes through the core. The outer layer grain size is fine and the strength is higher, thereby improving the material strength.
[0027] The use of low-temperature heating steel rolling technology can save the consumption of heating energy such as gas, which is conducive to low-carbon environmental protection.
[0028] The resistivity of the electrode steel of the present invention is distributed in a gradient, with low resistivity in the center and high resistivity on the surface. According to the current characteristics, the area with low current is selected to pass through. Therefore, during use, the current always passes through the center of the electrode steel, and the surface of the electrode steel does not pass current and suffers no loss, thereby extending the service life. DETAILED DESCRIPTION
[0029] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0030] A specific embodiment provides a gradient ultra-low resistivity electrode steel, the mass percentage of which is as follows: C: 0.001-0.003%, Si: 0.0005-0.001%, Mn: 0.008-0.01%, P≤0.006%, S≤0.002%, O: 0.002-0.003%, Cu: 4.3-5.2%, and the rest is Fe and impurity elements.
[0031] In the optimized scheme, the mass percentages of the components are: C: 0.001-0.003%, Si: 0.0005-0.001%, Mn: 0.008-0.01%, P≤0.006%, S≤0.002%, O: 0.0005-0.001%, Cu: 4.3-5.2%, and the rest are Fe and impurity elements.
[0032] The present invention adopts steel composition design to deeply remove C, Si and Mn elements in the steel, thereby reducing the hindering effect of impurity elements in the steel on the flow of electrons; adopts ultra-low O elements to reduce the presence of oxides in the steel and reduce the hindering effect of oxides on the movement of electrons; adds 4.3-5.2% of Cu elements to fill atomic vacancies and increase the conductivity of the phase interface, thereby improving the conductive performance of the material. Compared with ordinary Q195 material, the resistivity is reduced by more than 35%.
[0033] The specific embodiment also provides a method for manufacturing the above-mentioned gradient low resistivity electrode steel, including the steps of molten iron desulfurization, converter smelting, LF furnace refining, RH vacuum treatment, continuous casting, heating, rolling, and cooling;
[0034] The converter smelting time is 30-35 minutes, the two-time slag removal process is adopted, the steel tapping temperature is 1610-1620°C, and Cu is added during the steel tapping process; the LF furnace refining slag basicity is controlled to be 3.2-3.7, and the LF furnace treatment time is not less than 30 minutes; the RH vacuum treatment decarburization time is greater than 16 minutes, and the oxygen content off the station is 0.0006-0.0008%; the tundish temperature is controlled to be 1550-1570°C, and the cross-sectional size of the ingot is 280×380mm; the ingot heating temperature is 830-850°C, and the heating time is 160-210min; the starting rolling temperature of the rough rolling is ≤800°C; the final rolling temperature of the fine rolling is ≤680°C, and the square steel is rolled into (170-230)×(120-160)×(2000-2100)mm long; natural cooling is performed after rolling, and the cooling rate is 0.2-0.8°C / s.
[0035] The invention controls the heating temperature of the ingot to 830-850°C, controls the final rolling temperature to be ≤680°C, and rolls the ingot into square steel with a length of (170-230)×(120-160)×(2000-2100) mm by low temperature rolling. The finished product forms a grain size gradient from the core to the surface, wherein the core grains are coarse and the surface grains are fine, and the grain size gradually increases from level 1 to level 5 from the core to the surface. Since the core grain size is large and the electrical conductivity is strong, the current selectively passes through the core. The outer layer grain size is fine and the strength is higher, thereby improving the material strength.
[0036] In the optimized solution, the tapping temperature of the steel is controlled to be 1615-1618°C during the second slag removal in the converter smelting step.
[0037] In the optimized solution, the LF furnace refining step has a leaving station temperature of 1690±10°C.
[0038] In the optimized scheme, the RH vacuum treatment step adopts a deep vacuum degree of ≤60Pa and a treatment time of ≥16min.
[0039] In the optimized scheme, the continuous casting step adopts a large tank long nozzle and a crystallizer immersed nozzle protection casting, and the immersion depth is 82-92 mm; the temperature of the molten steel in the middle package is controlled to be 20-35°C above the liquidus temperature line of the steel grade; and the billet drawing speed is controlled to be 0.5-0.7 m / min.
[0040] In the optimized solution, the heating step controls the heating temperature of the ingot to be 845-850°C.
[0041] In the optimized solution, the starting rolling temperature in the rough rolling step is controlled to be 780-800°C. In the finishing rolling step, the final rolling temperature is controlled to be 650-680°C.
[0042] In the optimized solution, the cooling step is performed at a cooling rate of 0.7-0.8°C / s to room temperature.
[0043] Example 1
[0044] A gradient ultra-low resistivity electrode steel, the chemical composition by weight ratio is: C: 0.002%, Si: 0.0008%, Mn: 0.009%, P: 0.002%, S: 0.001%, O: 0.0006%, Cu: 4.35%, and the rest is Fe and impurity elements. The production process is as follows:
[0045] 1) Carry out hot metal desulfurization and converter smelting, use double slag removal, add Cu plate when 1 / 4 of the steel is tapped, and control the tapping temperature at 1612℃;
[0046] 2) Add active lime and other substances to make white slag, control the slag basicity at 3.2, and the LF furnace treatment time is 32 minutes;
[0047] 3) RH vacuum treatment: deep vacuum, pressure 58Pa, treatment time 17min, oxygen content at the exit station 0.0006%;
[0048] 4) The cross-sectional size of the ingot is 280×380mm, and the casting is protected by a large tank long nozzle and a crystallizer immersion nozzle, with an immersion depth of 83mm; the temperature of the molten steel in the tundish is controlled at 1555℃; the ingot drawing speed is controlled at 0.6m / min;
[0049] 5) naturally stacking and cooling the ingot to room temperature;
[0050] 6) Heating the ingot, controlling the heating temperature to 830°C and the heating time to 170 min;
[0051] 7) Performing rough rolling and controlling the starting rolling temperature at 780°C;
[0052] 8) Finish rolling controls the final rolling temperature to 660°C; rolling into square steel with a length of 170×150×2030mm;
[0053] 9) After rolling, the cooling rate is 0.4℃ / S until it cools to room temperature.
[0054] Example 2
[0055] A gradient ultra-low resistivity electrode steel, the chemical composition by weight ratio is: C: 0.001%, Si: 0.0005%, Mn: 0.008%, P: 0.003%, S: 0.001%, O: 0.0007%, Cu: 4.5%, and the rest is Fe and impurity elements. The production process is as follows:
[0056] 1) Carry out hot metal desulfurization and converter smelting, use double slag removal, add Cu plate when 1 / 4 of the steel is tapped, and control the tapping temperature at 1618℃;
[0057] 2) Add active lime and other materials to make white slag, control the slag basicity at 3.3, and the LF furnace treatment time is 35 minutes;
[0058] 3) RH vacuum treatment: deep vacuum, pressure 56Pa, treatment time 18min, oxygen content at the exit station 0.0007%;
[0059] 4) The cross-sectional size of the ingot is 280×380mm, and the casting is protected by a large tank long nozzle and a crystallizer immersion nozzle, with an immersion depth of 82mm; the temperature of the molten steel in the tundish is controlled at 1560℃; the ingot drawing speed is controlled at 0.5m / min;
[0060] 5) naturally stacking and cooling the ingot to room temperature;
[0061] 6) Heat the ingot, control the heating temperature to 840°C, and the heating time to 180 min;
[0062] 7) Performing rough rolling and controlling the starting rolling temperature at 790°C;
[0063] 8) Finish rolling controls the final rolling temperature to 650°C; rolling into square steel with a length of 170×150×2030mm;
[0064] 9) After rolling, the cooling rate is 0.5℃ / S until it cools to room temperature.
[0065] Example 3
[0066] A gradient ultra-low resistivity electrode steel, the chemical composition by weight ratio is: C: 0.003%, Si: 0.0009%, Mn: 0.01%, P: 0.001%, S: 0.001%, O: 0.0007%, Cu: 5.1%, and the rest is Fe and impurity elements. The production process is as follows:
[0067] 1) Carry out hot metal desulfurization and converter smelting, use double slag removal, add Cu plate when 1 / 4 of the steel is tapped, and control the tapping temperature at 1617℃;
[0068] 2) Add active lime and other materials to make white slag, control the slag basicity at 3.7, and the LF furnace treatment time is 38 minutes;
[0069] 3) RH vacuum treatment: deep vacuum, pressure 55Pa, treatment time 19min, oxygen content at the exit station 0.0008%;
[0070] 4) The cross-sectional size of the ingot is 280×380mm, and the casting is protected by a large tank long nozzle and a crystallizer immersion nozzle, with an immersion depth of 92mm; the temperature of the molten steel in the tundish is controlled at 1568℃; the ingot drawing speed is controlled at 0.7m / min;
[0071] 5) naturally stacking and cooling the ingot to room temperature;
[0072] 6) Heat the ingot, control the heating temperature to 845°C, and the heating time to 200 min;
[0073] 7) Performing rough rolling and controlling the starting rolling temperature at 770°C;
[0074] 8) Finish rolling controls the final rolling temperature to 660°C; rolling into a square steel with a length of 170×150×2030mm;
[0075] 9) After rolling, the cooling rate is 0.7℃ / S until it cools to room temperature.
[0076] The gradient ultra-low resistivity electrode steel produced in Examples 1 to 3 was compared with Q195 and rolled into square steels with a length of 170×150×2030 mm. Comparison steel 1 has a composition of 0.15% C, 0.42% Mn, 0.22% Si, 0.012% P, and 0.003% S; comparison steel 2 has a composition of C: 0.16%, Si: 0.25%, Mn: 0.53%, P: 0.008%, and S: 0.003%. The resistivity and organization comparison of the above five steel components at different locations are shown in Table 1.
[0077] Table 1
[0078]
[0079] It can be seen from Table 1 that the resistivity of the present invention is significantly reduced by about 40% compared with the comparative example, and a gradient is formed between the resistivity and the grain size.
Claims
1. A method for manufacturing a gradient low resistivity electrode steel, characterized in that It includes hot metal desulfurization, converter smelting, LF furnace refining, RH vacuum treatment, continuous casting, heating, rolling and cooling steps; The mass percentage of chemical composition: C:
0. 001~0.003%, Si: 0.0005~0.001%, Mn: 0.008~0.01%, P≤0.006%, S≤0.002%, O: 0.0005~0.001%, Cu: 4.3~5.2%, and the rest are Fe and impurity elements; The converter smelting time is 30-35min, the slag removal process is twice, the tapping temperature is 1610-1620℃, and Cu is added during the tapping process. The basicity of LF furnace refining slag is controlled at 3.2~3.7, and the LF furnace treatment time is not less than 30min; The decarburization time of RH vacuum treatment is greater than 16 minutes, and the oxygen content at the exit is 0.0006-0.0008%; The temperature of the tundish is controlled at 1550-1570℃, and the cross-sectional size of the ingot is 280×380mm; The heating temperature of the casting is 830-850℃, and the heating time is 160-210min; The starting rolling temperature of the rough rolling is 780-800°C; the final rolling temperature of the fine rolling is 650-680°C, and the steel is rolled into square steel of (170-230)×(120-160)×(2000-2100) mm in length; the steel is naturally cooled after rolling, and the cooling rate is 0.2-0.8°C / s.
2. The method for manufacturing the gradient low resistivity electrode steel according to claim 1, characterized in that In the converter smelting step, the tapping temperature is controlled to be 1615-1618°C by the secondary slagging process.
3. The method for manufacturing the gradient low resistivity electrode steel according to claim 1, characterized in that In the LF furnace refining step, the leaving station temperature is 1690±10°C.
4. The method for manufacturing a gradient low resistivity electrode steel according to claim 1, characterized in that In the RH vacuum treatment step, the treatment time is ≥16 min with a vacuum degree of ≤60 Pa.
5. The method for manufacturing the gradient low resistivity electrode steel according to claim 1, characterized in that In the continuous casting step, a large tank long nozzle and a crystallizer immersion nozzle are used for protection casting, and the immersion depth is 82-92 mm; the temperature of the molten steel in the tundish is controlled to be 20-35° C. above the liquidus temperature line of the steel grade; and the casting billet drawing speed is controlled to be 0.5-0.7 m / min.
6. The method for manufacturing a gradient low resistivity electrode steel according to claim 1, characterized in that In the heating step, the heating temperature of the ingot is controlled to be 845-850°C.
7. The method for manufacturing a gradient low resistivity electrode steel according to claim 1, characterized in that In the cooling step, the cooling speed is 0.7-0.8°C / s to cool to room temperature.
Citation Information
Patent Citations
Method for the production of a siderurgical product made of carbon steel with a high copper content, and siderurgical product obtained according to said method
CN1633509A